Assessment of Significant Causes to School Building Defects - Othuman Mydin, M.A.; Agus Salim, N.A.; Tan, S.W.; Tawil, N.M.; Md Ulang, N. (EDP Sciences, 2014)
This paper focuses on the contribution factors of building defects in Malaysian school buildings. There are several building defects commonly found in Malaysia school buildings. In fact, building defects are becoming ordinary phenomena in the construction industry which results in negative impacts on schools, in the means of building performance, health and safety aspects and overall environment conditions as well as teaching and learning processes. Thus, a study is planned to identify the common building defects faced by school buildings in Kedah, Malaysia. Then, a thorough inspection is conducted and the respective defects are recorded with the aid of photographic. As the outcomes from the interview between researcher and person-in-charge from some schools, the main factors contributing to those building defects had been determined. Besides, appropriate mitigation solutions on the building defects have been offered, which are extremely essential in retaining a healthy and serviceable school building.